Investigating of Factors Affecting Tax Payers Compliance: The Moderating Role of Tax Authorities’ Moral Obligations - Ratnawati, Vince; Rusli, Rusli; Wahyuni, Nita (Archives of Business Research, 2021)
This study aims to investigates the effect of the tax authorities’ attitude, and the effectiveness of the taxation system on tax compliance. This study also wants to investigates the moderating role of the tax authorities’ moral obligations on the effect of the tax authorities’ attitudes and the effectiveness of the taxation system on taxpayer compliance. The population in this study are non-employee individual taxpayers who are registered at the Primary Tax Service Office in Pekanbaru. The sampling technique in this study used purposive sampling. To test the direct effect of the tax authorities’ attitude and the effectiveness of the taxation system, multiple regression analysis was used, while to test the moderating role of the tax authorities’ morale obligation, moderated regression analysis was used. The results show that the attitude of the tax authorities and the effectiveness of the taxation system affect taxpayer compliance. This study also found that the tax authorities’ morale obligations moderated the effect of the tax authorities’ attitude and the effectiveness of the taxation system on taxpayer compliance.